Comparison of Blood Glucose Testing Methods: Analyzer, Glucometer, and Spectrophotometer at Kuta Alam Health Center - Putri, Safridha Kemala; Fajarna, Farah; Ulya, Rozatul (Universitas Syiah Kuala, 2025)
Blood glucose, a form of sugar present in the bloodstream, is derived from dietary carbohydrates and stored as glycogen in the liver and skeletal muscles. Blood glucose levels of 140 mg/dL in random testing or 120 mg/dL in fasting tests the indication of diabetes mellitus (DM). According to the World Health Organization (WHO) in 2021, DM is among the top ten leading causes of death globally. Blood glucose levels can be measured using various methods, including chemistry analyzers, glucometers, and spectrophotometers. This study aims to evaluate the differences in blood glucose levels obtained using these three analytical methods. The study aims to compare blood glucose levels measured using a chemistry analyzer, glucometer, and spectrophotometer. A descriptive research method was applied, with samples collected through random sampling, comprising 25 normal and 25 elevated blood glucose level samples. The majority of participants were women (76.0 %, n=38), while men represented 24.0 % (n=12), with an average participant age of 57.8 years. In the normal group, blood glucose levels measured using the chemistry analyzer ranged from 72 mg/dL to 116 mg/dL, with a mean of 90.52 mg/dL. Measurements using the glucometer showed a range of 75 mg/dL to 129 mg/dL, with a mean of 95.88 mg/dL, while the spectrophotometer results ranged from 74 mg/dL to 120 mg/dL, with a mean of 93.00 mg/dL. In the high blood glucose group, measurements using the chemistry analyzer ranged from 195 mg/dL to 342 mg/dL, with a mean value of 272.04 mg/dL. Measurements with the glucometer ranged from 200 mg/dL to 358 mg/dL, with a mean value of 278.44 mg/dL, while the spectrophotometer results ranged from 199 mg/dL to 354 mg/dL, with a mean value of 275.48 mg/dL. Based on the results, the chemistry analyzer demonstrated higher precision and accuracy in measuring blood glucose levels compared to the glucometer and spectrophotometer.